Antenatal exposure to betamethasone: psychological functioning and health related quality of life 31 years after inclusion in randomised controlled trial. Issue 7518 (5th September 2005) - Dalziel, Stuart R; Lim, Vanessa K; Lambert, Anthony; McCarthy, Dianne; Parag, Varsha; Rodgers, Anthony; Harding, Jane E
Abstract: Objectives To determine if antenatal exposure to betamethasone for the prevention of neonatal respiratory distress syndrome alters psychological functioning and health related quality of life in adulthood. Design Follow-up of the first and largest double blind, placebo controlled, randomised trial of a single course of antenatal betamethasone for the prevention of neonatal respiratory distress syndrome. Setting Tertiary obstetric hospital in Auckland, New Zealand. Participants 192 adult offspring, mean age 31 years, of mothers who took part in a randomised controlled trial of antenatal betamethasone for the prevention of neonatal respiratory distress syndrome (87 exposed to betamethasone and 105 exposed to placebo). Interventions Mothers received two doses of betamethasone or placebo 24 hours apart. Main outcome measures Cognitive functioning assessed with Wechsler abbreviated scale of intelligence; working memory and attention assessed with Benton visual retention test, paced auditory serial addition test, and Brown attention deficit disorder scale; psychiatric morbidity assessed with Beck depression inventory II, state-trait anxiety inventory, and schizotypy traits questionnaire; handedness assessed with Edinburgh handedness inventory; health related quality of life assessed with short form 36 health survey. Results No differences were found between groups exposed to betamethasone and placebo in cognitive functioning, working memory and attention, psychiatric morbidity, handedness, or health related quality of life. Conclusions Prenatal exposure to a single course of betamethasone does not alter cognitive functioning, working memory and attention, psychiatric morbidity, handedness, or health related quality of life in adulthood. Obstetricians should continue to use a single course of antenatal betamethasone for the prevention of neonatal respiratory distress syndrome.